2005
DOI: 10.1029/2005ja011041
|View full text |Cite
|
Sign up to set email alerts
|

Pc 1 waves and associated unstable distributions of magnetospheric protons observed during a solar wind pressure pulse

Abstract: [1] We present observations of Pc 1 waves ($0.6 Hz) that occurred shortly after a strong (>20 nPa) compression of Earth's magnetosphere at 1321 UT, 18 March 2002. Intense Pc 1 waves were observed at several high-latitude ground stations in Antarctica and Greenland from 1321 UT to beyond 1445 UT. Two wave bursts were recorded at the Polar satellite at 1338 and 1343-1344 UT as it passed outbound in the Southern Hemisphere at 1154 local time (SM magnetic latitude of À22°and near L = 7.5) in good magnetic conjunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 42 publications
2
64
1
3
Order By: Relevance
“…This suggests that the suprathermal plasma plays an important role in destabilization of a more energetic RC and/or plasma sheet H + , and the high energy anisotropic RC and/or plasma sheet proton distributions appear to be a necessary but not sufficient condition for occurrence of EMIC waves. Similarly, studying Pc 1 -2 events in the dayside outer magnetosphere, Engebretson et al [2002] and Arnoldy et al [2005] found that greatly increased fluxes of low energy protons were crucial for destabilization of the higher energy anisotropic RC protons. The analysis by Engebretson et al [2007] suggests that the ion cyclotron wave growth rate could be significantly increased by the addition of cool/ suprathermal H + consistent with their observations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that the suprathermal plasma plays an important role in destabilization of a more energetic RC and/or plasma sheet H + , and the high energy anisotropic RC and/or plasma sheet proton distributions appear to be a necessary but not sufficient condition for occurrence of EMIC waves. Similarly, studying Pc 1 -2 events in the dayside outer magnetosphere, Engebretson et al [2002] and Arnoldy et al [2005] found that greatly increased fluxes of low energy protons were crucial for destabilization of the higher energy anisotropic RC protons. The analysis by Engebretson et al [2007] suggests that the ion cyclotron wave growth rate could be significantly increased by the addition of cool/ suprathermal H + consistent with their observations.…”
Section: Discussionmentioning
confidence: 99%
“…(Note that the most intense burst of Pc 1 waves studied by Arnoldy et al [2005] had a local normalized frequency X = 0.2, so the waves were on He + -branch.) For the purpose of comparison with our previous results, in the present study we kept the ion percentage the same as before, i.e., 77% + -mode is well beyond the scope of the current study, and it should be done separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMIC waves can cause rapid scattering and loss for ring current ions (Jordanova et al 2001b) and relativistic electrons above 0.5 MeV (Thorne and Kennel 1971;Lyons and Thorne 1973;Albert 2003;Summers and Thorne 2003;Meredith et al 2003b). Favored regions for EMIC excitation include the overlap between the ring current and the plasmasphere (Pickett et al 2010), dayside drainage plumes (Morley et al 2009), and the outer dayside magnetosphere in association with solar wind pressure fluctuations (Arnoldy et al 2005;Usanova et al 2008;McCollough et al 2009). Theoretical global modeling of EMIC wave excitation has confirmed the plasmapause and plume as favored regions of cyclotron resonant instability (Jordanova et al 2007;Chen et al 2010a) and demonstrated that the wave excitation can also be enhanced by density fluctuations within a plume (Chen et al 2009a).…”
Section: Fig 2 Spectrogram Of Waves Observed On Combined Release Andmentioning
confidence: 99%
“…The hot H + distribution, with a temperature anisotropy sufficiently high to satisfy the EMIC instability, is called the wave free-energy provider [e.g., Cornwall, 1965;Rauch and Roux, 1982]. Besides contributing to the increase of the EMIC wave growth rate, energetic H + are able to greatly modify the real part of the wave dispersion relation, dramatically changing the wave generation [e.g., Arnoldy et al, 2005;Engebretson et al, 2007;Gamayunov and Khazanov, 2008].…”
Section: Introductionmentioning
confidence: 99%